Influence of linear-sprint performance, concentric power and maximum strength on change of direction performance in elite youth soccer players - Kadlubowski, B.; Keiner, M.; Stefer, T.; Kapsecker, A.; Hartmann, H.; Wirth, K. (German Journal of Exercise and Sport Research, 2021)
Change of direction (COD) performance has an essential role in soccer. In the literature, there is a wide range of explained variance in correlation analyses between linear-sprint performance, concentric power and maximum strength and COD performance. Therefore this study has (1) analyzed the influence of linear-sprint performance, concentric power and maximum strength on COD performance in elite youth soccer players and (2) compared the calculated influence on the different COD tests. To answer the research questions, 67 elite youth soccer players were tested. The linear-sprint (10m, [LS]) performance, concentric power (squat jump [SJ]) and maximum strength (1 repetition maximum [1RM]) and COD (measured via the Illinois agility test [IAT], the 505 agility test [505], the agility test of the German Soccer Association [GewT], and the triangle test [TriT]) were assessed. The Pearson correlation analysis was used to assess the relationship. Benjamini and Hochberg`s method, which was used to control the study-wise false discovery rate, was 0.05. The LS performance had the greatest impact on COD performance with a wide range of explained variance between the different COD tests (r2= 0.18 to 0.39). However, SJ compared to LS performance had lower influence, but also a wide range of explained variance (r2= -0.02 to -0.29). Correlations for 1RM and COD test were calculated with r2= -0.01 to -0.09. Thus, (1) the greater the similarity between the performance tests (i.e., LS, SJ, 1RM) and the COD tests, the higher the explained variance between the variables in question. Furthermore, (2) as the different COD tests are affected to different degrees by linear-sprint, concentric power and maximum strength performance, it might be concluded that the tests have a different physiological requirement profile. Therefore, coaches and sport scientists must review and select different tests with logical validity, based on the requirement profiles of soccer.